Pengelolaan Sampah di Kabupaten Bogor: Tantangan dan Solusi - Suryana, Nanang; Tjenreng, Muhammad Baharuddin Zubakhrum (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Waste management has become one of the significant environmental issues in Indonesia, including in Bogor Regency. The growing waste, both from the household and industrial sectors, has a negative impact on cleanliness, health, and the quality of life of the community. Bogor Regency, as one of the areas with a high population density and rapid development, faces a major challenge in waste management. This journal aims to identify the issues surrounding waste management in Bogor Regency and provide recommendations for sustainable solutions. Based on statistical data and literature studies, it was found that the lack of adequate waste management infrastructure and low public awareness are the main factors contributing to this problem.